Implikasi Makna Ritus Syahattu Engget bagi Germita Jemaat Ayalon Pangeran - Sudirman Porobaten; Wolter Weol; Semuel Selanno (Jurnal Ilmiah Wahana Pendidikan, 2021)
The aims of this study are (1) to analyze the views of the Germita Jamaat Ayalon Pangeran regarding the Syahattu Engget Ritual. (2) To find out the values ​​of the Syahattu Engget Rite in the Germita Congregation of Ayalon Pangeran. (3) To find out the involvement of the members of the Germita Ayalon Pangeran congregation in the practice of the Syahattu Engget Ritual. This research approach is qualitative by using data collection procedures and techniques: (1) observation, (2) in-depth interviews, (3) documentation. Data analysis used the following steps: (1) data reduction, (2) data display, (3) checking the validity of the data. Based on the analysis of the data, it was concluded: (1) Germita Jemaat Ayalon Pangeran believes that the Syahattu Engget Ritual is a ritual that must be preserved and must not be removed and has certain values ​​for the Germita Congregation of Ayalon Pangeran (2) The Syahattu Engget traditional event has certain values. the rite values ​​contained therein are sacred values, social values, psychological values, religious phenomenological values, and Christian theology values ​​(3) The involvement of the Germita Ayalon Pangeran Jama'at on the rite is very high and even followed by the entire congregation. Based on these conclusions, it is recommended (1) to be more enthusiastic in carrying out service tasks, especially to preserve the culture that has been passed down by the ancestors so that it can be implied in everyday life for the Germita of the Ayalon Pangeran congregation (2) Be more consistent in maintaining the customs inherited from the ancestors in this case the Syahattu Engget rite, reactivates other cultures that are starting to be lost or eroded over the development of this era of globalization (3) The results of this study can be used as a reference or reference for conducting further relevant research as an effort to preserve the nation's culture (4) As for The weaknesses of the results of this study can be used as study material for further research.